Calidad de vida y capacidades funcionales de una paciente adulta mayor - Reyna Alburqueque, Kimberly Pamela (2019)
The research had as its theme: Quality of life and functional abilities of an elderly patient. With the study of the investigated phenomenon, it was determined that, if there is a degree of negative affectation in the psychological, physical and social areas, produced particularly by depression As a result of the deterioration of their physical capacity and the decline of self-esteem, people's well-being includes the personal satisfaction of the individual in the performance of daily activities. The instruments used in the research, Seville Questionnaire on Quality of Life, Test of Instrumental Activities of Daily Life and the Geriatric Depression Scale fully complied with their purposes, contributing to the diagnosis of the disorder the patient was suffering as well as the guidelines clinics to follow for the therapeutic intervention process, thus, the research had the scope proposed in the objectives, a definition was achieved on the meaning of the quality of life and the importance of this functional development, moreover it was proposed as an additional goal that the patient conceptualize a sense of life